Malicious Peace: Violent Criminal Organizations, National Governments and Truces - Kan, Paul Rexton (International Journal of Criminology and Sociology, 2014)
Truces among violent criminal organizations, like gangs and organized crime syndicates, which occur with national government support fall into a unique gap between understandings of crime and internal state violence. Recent national level gang truces in Central America and the Caribbean fall into this gap; the truces are designed to lower homicide rates and move some members of criminal groups towards legal activities. However, there is precious little research examining multiple truces in different countries as a group so that lessons may be drawn for other countries suffering from high levels of violence at the hands of criminal organizations. With violent criminal organizations as the main threat to the national security of many states, shedding light on how to reduce extreme levels of violence is vital. Close examination of attempted and implemented truces in Belize, El Salvador, Guatemala, Honduras and Trinidad and Tobago reveals that a constellation of factors leads national governments to be receptive to such agreements and violent criminal groups to accede to them.